2014
DOI: 10.7150/ijbs.8879
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage Polarization in Inflammatory Diseases

Abstract: Diversity and plasticity are two hallmarks of macrophages. M1 macrophages (classically activated macrophages) are pro-inflammatory and have a central role in host defense against infection, while M2 macrophages (alternatively activated macrophages) are associated with responses to anti-inflammatory reactions and tissue remodeling, and they represent two terminals of the full spectrum of macrophage activation. Transformation of different phenotypes of macrophages regulates the initiation, development, and cessa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
671
0
6

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 839 publications
(736 citation statements)
references
References 102 publications
18
671
0
6
Order By: Relevance
“…Signaling via Mas modulates the delicate balance between M(LPS+IFNγ)-like and M(IL-4+IL-13)-like macrophages, pushing it toward the M(IL-4+IL-13)-like phenotype, which is an important regulator controlling inflammation and autoimmunity (32,33). Therefore, the receptor Mas may be an interesting therapeutic target to treat autoimmune diseases via regulating inflammatory processes.…”
Section: Discussionmentioning
confidence: 99%
“…Signaling via Mas modulates the delicate balance between M(LPS+IFNγ)-like and M(IL-4+IL-13)-like macrophages, pushing it toward the M(IL-4+IL-13)-like phenotype, which is an important regulator controlling inflammation and autoimmunity (32,33). Therefore, the receptor Mas may be an interesting therapeutic target to treat autoimmune diseases via regulating inflammatory processes.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, once started the resolution of this process, macrophages acquire anti-inflammatory action, with an increase in the expression of cytokines IL-10 and TNF-, in addition to start a process of tissue repair -a characteristic called alternative activation or M2 (LIU et al, 2014). In M1 inflammatory macrophages, the effect of polarization is performed by the Th1 cell, or natural killer, derived from IFN-gamma, along with TFN-↵.…”
Section: Macrophage In Sepsismentioning
confidence: 99%
“…Current thinking suggests that the M1-M2 paradigm likely represents an extreme of macrophage phenotypes and is over simplistic [2]. Evidence suggests that macrophage phenotypes are not static but dynamic and tissue microenvironment-dependent and diseases play a role in the polarization of macrophages [3][4][5]. It has been shown that M1 and M2 macrophages can switch their phenotype based on the tissue microenvironment [6].…”
Section: Introductionmentioning
confidence: 99%